The Defectiveness of Spruce Stands in the Northern Taiga Zone of the Arkhangelsk Region - Sergey V. Koptev; Sergey A. Vaskin (Лесной журнал)
The results of studying the defectiveness of spruce forests in the northern taiga zone of the Arkhangelsk Region are presented. Defectiveness has a significant impact on the sanitary condition, marketability and sustainability of forest plantations. The study has been conducted from 2020 to 2023 using materials obtained from sample plots laid in mature spruce plantations, modal in terms of basic taxation parameters. Before starting the field work, the cartographic databases have been studied. The sample size has been determined by the variability of the taxational diameter of the main species and the experiment accuracy. In each test area, all trees have been enumerated by species, diameter at a height of 1.3 m and by condition categories. For each tree, the presence of defects affecting marketability and fruit bodies of wood-destroying fungi has been noted. To determine the age of the trees in the sample plot, core samples have been taken from the root collar. To study the patterns of the defectiveness spread and obtain mass material, statistical survey sites have been laid on fresh cuttings. When rot has been detected on the stump, the diameter of the rot has been measured and its type and stage have been determined. The age of the trees has been determined by the annual rings on the stumps. In the presence of rot, age has been determined by correlation with the diameter of the stump. The trees have then been grouped by their respective age classes. In the course of the research, defectiveness indicators have been studied and analyzed in various forest growth conditions. It has been revealed that with an increase in the age class, the occurrence of all defects increases. The most obvious dependence has been recorded for rots. The amount of rots varies from 5.1 to 29.0 %, depending on the type of forest growth conditions. The proportion of rots decreases with the deterioration of forest conditions. The most common wood-destroying fungus is the root sponge (Heterobasidion annosum (Fr.) Bref.). There is an increase in the incidence of wood-destroying fungi in trees with increasing diameter. The average stage of butt rot has been 2.8. The study of the defectiveness will improve the accuracy of assessing the resource potential of coniferous plantations in the Arkhangelsk Region.